AKIBAT HUKUM PELAKSANAAN GANTI KERUGIAN PENGADAAN TANAH YANG DITITIPKAN DI PENGADILAN NEGERI (STUDI KASUS PUTUSAN NOMOR: 27/Pdt.G/2020/PN Tjs) - Febryani, Ferra; Silviana, Ana (Pagaruyuang Law Journal, 2026)
This study examines the legal consequences of depositing compensation funds (consignation) in the land acquisition process that resulted in a tort lawsuit, as decided in Verdict Number 27/Pdt.G/2020/PN Tjs. Under land acquisition regulations, depositing compensation with the District Court should nullify the land rights of the holder and transfer the land status to state land. However, in this case, the panel of judges determined that the defendants’ actions constituted an unlawful act because they took over the land without identifying the rightful owner. Through evidence and findings from the on-site inspection, the plaintiff was recognized as the party in actual possession of the land, meaning the loss of land rights occurred as a harmful legal consequence to the plaintiff. This decision reinforces the application of Articles 1365 to 1367 of the Indonesian Civil Code, which state that any unlawful act causing harm must be compensated, including losses arising from negligence or actions committed by individuals under the defendant’s responsibility. Therefore, the consignation mechanism in land acquisition must be carried out carefully and cannot be used as the basis for taking over land without proper identification of the rightful owner, in order to prevent civil disputes and avoid further legal liability.